Individualization of approaches to managing patients during menopausal transition - Т. Ф Татарчук; В. І. Пирогова; О. О. Єфіменко; О. В. Булавенко; І. М. Антонян; Г. Я. Пілягіна (Publishing House TRILIST, 2018)
The global aging of the population leads to a significant increase in the demographic burden on society, puts a heavy burden on the economy and causes significant structural changes in the sphere of social security. Therefore, the problem of maintaining the health of women in peri- and post-menopause becomes extremely important for public health and health. It is in this period that a number of somatic and mental diseases appear that significantly affect the quality and overall life span of a woman. Inevitably, menopausal manifestations is a change in hormone levels that causes various symptoms, including vasomotor disorders, bone density, hair loss, decreased sexual interest and mood, etc. Therefore, the development of therapeutic and rehabilitative programs for women of menopausal age, based on pathogenetically substantiated complex treatment. Among other things, patients in the phase of the menopausal transition need to take into account several principal provisions: - Clinical deficiency of sex hormones (estrogens, progesterone and testosterone) in women is an indication for the appointment of menopausal hormone therapy (MHT) with appropriate hormones. This should be done as soon as possible (during the menopausal transition) and personified - taking into account the individual characteristics of patients. The purpose of MHT should correspond to the symptomatology and goals of the prevention of various diseases, as well as the history, research results, preferences and expectations of women. - Women who need correction of the symptoms of menopause and adequate control of the endometrium, should be prescribed a combination of estrogen and gestogen. In the presence of risk factors for hyperproliferation, the best choice is the combination of estrogen and progestogens with antiproliferative activity, for example levonorgestrel, which can be prescribed both in combination menopausal therapy and in the form of an intrauterine system with this gestogen. - A special category is patients who have clinical manifestations of androgen deficiency in the clinical situation, in addition to the characteristic symptoms of estrogen deficiency. In such patients, preference should be given to the drug containing levonorgestrel, which has residual androgenic activity, provides adequate control of the endometrium and has additional advantages with regard to the prevention of osteoporosis, premature ovarian failure and cognitive decline.